Determining Marketing Channel Preference: A Case Study of Chocolate Drink’s Consumer Preferences - Moh Wahyudin; Firda Safira Yulianti; Wagiman Wagiman (Agroindustrial Journal, 2021)
Nowadays, e-commerce has become increasingly common among businesses. However, there is still a lack of determining marketing channel preferences between offline and online. Therefore, the company needs to consider the various factors that consumers consider when choosing a particular marketing channel. This study aims to find the marketing channels that consumers consider the most in buying instant chocolate drinks. The research was conducted in Indonesia and used the Analytic Hierarchy Process method to assess and determine the order of priority. The most preferred marketing channel by consumers to get instant chocolate drinks is the modern store. Then followed by the e-marketplace channel and social media channel.